India’s Defence Diplomacy In Peace Time To Build Defence Capabilities (Study Case: Quad) - KBG Sumudu Madutharanga1; Fauzia Gustarina Cempaka Timur; Surachman Surjaatmadja (CV. AFDIFAL MAJU BERKAH, 2024)
This study delves into the nuanced landscape of India's defense diplomacy, emphasizing its engagement in the Quadrilateral Security Dialogue (QUAD) as an interesting case study. QUAD serves as a platform for collaborative efforts aimed at fostering regional security and stability. Against the backdrop of geopolitical complexities and evolving global dynamics, India's peacetime defense diplomacy within QUAD unfolds as a multifaceted endeavor. This study aims to understand the diplomatic initiatives and policy frameworks used by India to strengthen its defense capabilities through strategic collaboration with QUAD partners that include joint military exercises, technology transfer, information sharing agreements and economic partnerships. This research uses qualitative research methods with a case study method to analyse India's defence diplomacy within the Quad framework. India's defense diplomacy within QUAD during peacetime has had a positive impact on its defense capabilities. Strategic alignment with broader national security objectives, technological advancements, strengthened regional security and economic resilience demonstrate the effectiveness of the QUAD framework. Nonetheless, challenges such as military asymmetry and geopolitical complexity remain, necessitating sustained efforts to enhance the effectiveness of defense diplomacy within QUAD. Sustained joint efforts and coordination of strategic objectives will be key for India to maximize its benefits and strengthen its position as a key player in the evolving Indo-Pacific security landscape.